2017
DOI: 10.18203/2320-6012.ijrms20173954
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Chlamydia trachomatis infection amongst infertile women compared with pregnant controls in North-central Nigeria

Abstract: Background: Female infertility due to tubal damage resulting from pelvic infections including Chlamydia trachomatis is common among women in our environment. The study aimed at determining the prevalence of Chlamydia trachomatis antibody amongst infertile women and to assess the relationship between exposure to Chlamydia trachomatis infection and tubal infertility in Garki Hospital, Abuja, Nigeria.Methods: This was a case control study among 76 infertile patients with tubal occlusion diagnosed with hysterosalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…They concluded that the clinical feature having the potential of identifying woman at high risk for Chlamydia infection were vaginal discharge (24.5%), followed by dysmenorrhea (24.5%) and lower abdominal pain (23.1%). (31) The present study also demonstrated that fallopian tube blockage is a risk factor for female infertility (OR=5.45, 95% CI= 1.75 -16.95, p=0.003). Fallopian tube blockage was much more common in secondary infertile females (20.4%) compared to only 9.3% of primary infertile.…”
Section: Risk Factors For Female Infertilitysupporting
confidence: 75%
See 1 more Smart Citation
“…They concluded that the clinical feature having the potential of identifying woman at high risk for Chlamydia infection were vaginal discharge (24.5%), followed by dysmenorrhea (24.5%) and lower abdominal pain (23.1%). (31) The present study also demonstrated that fallopian tube blockage is a risk factor for female infertility (OR=5.45, 95% CI= 1.75 -16.95, p=0.003). Fallopian tube blockage was much more common in secondary infertile females (20.4%) compared to only 9.3% of primary infertile.…”
Section: Risk Factors For Female Infertilitysupporting
confidence: 75%
“…(30) The present study found that symptoms suggestive of STIs were highly correlated with female infertility; dyspareunia (OR=7.04, 95% CI= 2.76 -17.95, p=0.001), while chronic lower abdominal pain or abnormal vaginal discharge increased the risk of infertility by more than three times. In Nigeria, Ogbu GI. et al (2017) studied the relationship between Chlamydia trachomatis infection and tubal infertility found a statistically significant association between positive C. trachomatis antibody titre among cases with tubal factor infertility (75.0%) compared with controls (22.2%).…”
Section: Risk Factors For Female Infertilitymentioning
confidence: 99%
“…et al (2017) studied the relationship between Chlamydia trachomatis infection and tubal infertility found a statistically significant association between positive C. trachomatis antibody titre among cases with tubal factor infertility (75.0%) compared with controls (22.2%). They concluded that the clinical feature having the potential of identifying woman at high risk for Chlamydia infection were vaginal discharge (24.5%), followed by dysmenorrhea (24.5%) and lower abdominal pain (23.1%) [ 37 ]. The present study also demonstrated that fallopian tube blockage is a risk factor for female infertility (OR = 5.45, 95% CI = 1.75–16.95, p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…However, higher prevalence estimates have been reported among women in low resource settings with tubal factor infertility i.e. (35.3%) [8] and 75% [26]. Both studies [8,26] utilised systemic antibody against C. trachomatis proteins which are more sensitive for previous C. trachomatis exposure unlike direct local antigen tests which detect current infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have linked C. trachomatis infection to infertility [5,8,26,28], there are no reports on the impact of active genital C. trachomatis infection on outcomes among women undergoing tubal flushing. This study found an association between active genital C. trachomatis infection and reduced clinical pregnancy and live birth rate among women who underwent tubal flushing.…”
Section: Discussionmentioning
confidence: 99%